Deposition Flux, Stocks of C, N, P, S, and Their Ecological Stoichiometry in Coastal Wetlands With Three Plant Covers - Du, Shudong; Bai, Junhong; Zhao, Qingqing; Wang, Chen; Guan, Yanan; Jia, Jia; Zhang, Guangliang; Yan, Chongyu (Frontiers in Ecology and Evolution, 2022)
The depositional flux of coastal wetlands and the deposition rate of biogenic elements greatly affect the carbon sink storage. Ecological stoichiometry is an important ecological indicator, which can simply and intuitively indicate the biogeochemical cycle process of the region. This study investigated the soil deposition flux, stocks, and ecological stoichiometric ratios of C, N, P, and S under different water and salt conditions based on 137Cs dating technology in the Yellow River Delta (YRD) of China. The results showed that the deposition fluxes were 0.38 cm/year for PV wetlands, 1.08 cm/yr for PA wetlands, and 1.06 cm/yr for SS wetlands. Similarly, PA wetlands showed higher deposition fluxes of C, N, and S compared with SS and PV wetlands. PA wetlands had higher stocks of C (5.86 kg/m2), N (0.36 kg/m2) and S (0.36 kg/m2) in the top 1-m soil layer compared with PV and SS wetlands. However, the highest deposition rate of P (9.82 g/yr/m2) was observed in SS wetlands among the three wetlands. Three accumulative hotspots of C, N, and S in soil profiles of PA and SS wetlands were observed at soil depths of 0–10, 40–60, and 90–100 cm, whereas one accumulative hotspot of P was at the soil depth of 10–12 cm in SS wetlands and 80–82 cm in PA wetlands. PV wetlands showed higher accumulations of C, P, and S in the top 10 cm soil layer and N at the soil depth of 90–100 cm. The higher top concentration factors in these three wetlands indicated that the dominant input of plant residues was the main reason. The ratios of C/N and C/N/P of each sampling site were higher in the surface soils and decreased with depth. The ratios of C/P and N/P were larger in the surface layer (0–20 cm), the middle layer (40–60 cm), and the deep layer (90–100 cm). The ratios of N/P and C/N/P were relatively lower, indicating that these studied wetlands were N-limited ecosystems. The results implied that the coastal wetlands in the YRD have huge storage potential of biogenic elements as blue carbon ecosystems.